Antioxidant effect of Legalon(r) SIL in ischemia-reperfusion injury of rat skeletal muscle - Ergün,Yusuf (2016)
PURPOSE: To evaluated the potential antioxidant agent Legalon (r) SIL (silibinin-C-2',3-bis(hydrogensuccinat)) in the skeletal muscle of rats. METHODS: IRI was achieved via tourniquet application in Wistar-albino rats. Experimental groups were chosen as (i) sham control, (ii) IRI (3+2 h), (iii) IRI and Legalon (r) SIL-50 (50 mg/kg/i.p.), (iv) IRI and Legalon (r) SIL-100 (100 mg/kg/i.p.), and (v) IRI and Legalon (r) SIL-200 (200 mg/kg/ i.p.). Muscle viability (evaluated by triphenyltetrazolium chloride dye method), malondialdehyde, superoxide dismutase, catalase, and glutathione peroxidase were assessed in muscle samples using a spectrophotometer. RESULTS: Although viability of the injured limb non-significantly declined in the IRI group, administration of Legalon (r) SIL did not prevent injury. However, dramatic increase observed in malondialdehyde levels in the IRI group was prohibited by Legalon (r) SIL in a statistically significant manner. In comparison with the sham-control group, IRI and Legalon (r) SIL administration did not cause any significant alterations in the levels of superoxide dismutase, catalase, and glutathione peroxidase. CONCLUSION: Although Legalon (r) SIL was not sufficient to prevent muscle injury in terms of viability, it is found to be an effective option to reduce reactive oxygen species-induced cell injury.